A PILOT STUDY FOR THE ESTIMATION OF ABOVE GROUND BIOMASS AND LITTER PRODUCTION IN Rhizophora mucronata DOMINATED MANGROVE ECOSYSTEMS IN THE ISLAND Of MAURITIUS - Shafiiq Abib; Chandani Appadoo (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Estimation of the above ground biomass of mangroves is an important issue because of its relevance to nutrient turnover and the potential to store carbon. Productivity, as indicated by litter fall rates is important to determine the rate at which mangroves produce new biomass. The aim of the current study was to estimate the above ground biomass and quantify litter fall in two Rhizophora mucronata dominated mangrove ecosystems of Mauritius located at Trou D’eau Douce (eastern side), and at Petite Riviere Noire on the (western side) of the island. Field studies were conducted from September 2011 to January 2012. Quadrats of 5 × 5 metres were set up in each site and 200 mature trees were surveyed. Sixteen litter traps were constructed and installed at the two sites for litter collection. To estimate the above ground biomass, allometric equations were used. The total above ground biomass for Trou D’eau Douce and Petite Riviere Noire were 26.96 t ha-1 and 16.63 t ha-1, respectively. The mean rate of litter fall for Trou D’eau Douce and Petite Riviere Noire were 3.2 ± 0.44 g DW m-2 day-1 and 4.07± 0.95 g DW m-2 day-1, respectively. This study is among the first to provide information on the estimation of above ground biomass for mangroves of Mauritius. It is also the first to provide data on the litter production in mangroves at Petite Riviere Noire and Trou D’eau Douce.